Skills for the 21st Century in Latin America and the Caribbean - Aedo, Cristian; Walker, Ian (World Bank, 2012)
There is growing interest, worldwide, in the link between education systems and the production of skills that are valued in the labor market. With growth stagnating and unemployment soaring in much of the world, educators are being asked to focus more on producing skills that feed into labor productivity and support the sustainable growth of employment and incomes. This timely volume contributes important new findings on the dynamics of education systems and labor market outcomes in Latin America and the Caribbean (LAC). It analyzes an important recent shift in labor market trends in LAC: the first decade of the 21st century has witnessed a marked decline in the earnings premia for university and secondary education. This, in turn, is contributing to reduced income inequality across the region. The recent trend contrasts with the sharp rise in tertiary earnings premia that was observed in the 1990s and that helped to reinforce high levels of income inequality in the region at that time. The authors recommend that, having achieved very large increases in secondary and tertiary enrollment, the region should now focus on improving the quality of its education systems and the pertinence of education curricula for the needs of the labor market. At age 15, the learning achievement of the average Latin American student still lags two years behind his or her Organization for Economic Co-operation and Development (OECD) contemporary. The study opens up an important agenda for future research. While the evidence presented on the trends in education earnings premia is clear, the conclusions about the causes and significance of those trends are largely based on suggestive evidence for a limited number of countries, and are not definitive because of data limitations. The findings call for further in-depth analysis of the nature of skill mismatches, to inform policies that can strengthen the region's future economic growth by enhancing the productivity and earnings potential of the workforce.